Facing death : where culture, religion, and medicine meet - Spiro, Howard M. (Howard Marget), 1924-2012; Curnen, Mary G. McCrea; Wandel, Lee Palmer (Yale University Press, 1996)
This is an important manual for those professionally involved with the dying, as well as a treatment & consolation for private readers. It brings together medical and humanities experts, to reflect on medical, cultural and religious responses to death.
"Prepared under the auspices of the Program for Humanities in Medicine, Yale University School of Medicine and the Goethe-Institut, Boston."
Keywords: Terminally ill.; Death -- Psychological aspects.; Death -- Religious aspects.; Death -- Moral and ethical aspects.; Death.; Medicine -- Religious aspects.; Professional ethics.; Terminal Care; Terminally Ill; Attitude to Death; Death; Religion and Medicine; Ethics, Professional; Malades en phase terminale.; Mort -- Aspect psychologique.; Mort -- Aspect religieux.; Mort -- Aspect moral.; Soins en phase terminale.; Mort.; Médecine -- Aspect religieux.; Déontologie professionnelle.; terminally ill.; deaths.; professional ethics.; SELF-HELP -- Death, Grief, Bereavement.; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement.; Professional ethics; Medicine -- Religious aspects; Death -- Moral and ethical aspects; Death -- Psychological aspects; Death -- Religious aspects; Terminally ill; Sterven.; Sociologische aspecten.; Stervensbegeleiding.